GAMBARAN KADAR KOLESTEROL TOTAL PADA PEROKOK AKTIF DI BANJAR BEKUL,DENPASAR SELATAN - Sastriani, Yosefa; Rinawati, Luh Putu; Wilankrisna, Luh Ade; Sarihati, I Gusti Agung Dewi (Jurnal Skala Husada : The Journal of Health, 2023)
Smoking habit is one of the leading causes of death in adults worldwide. Smoking will have a major effect on increasing cholesterol levels which will cause health problems, including coronary heart disease, coronary thrombosis, cancer, bronchitis or inflammation of the larynx, and death of the fetus. This caused by substances contained in cigarettes such as nicotine, carbon monoxide, tar, and other chemicals. This study aims to determine total cholesterol levels in active smokers in Banjar Bekul, South Denpasar District. This type of research is a descriptive study using a cross sectional approach. Examination of total cholesterol levels was carried out using the POCT (Point of care testing) method on capillary blood samples from 30 respondents. The results showed that the examination of total cholesterol levels in active smokers was in the normal category as much as 56.7%, high risk limit as much as 13.3%, high risk as much as 30.0%. Total cholesterol levels that exceed the normal limit are most commonly found in the age group 30 (33.3 %), the number of cigarettes per day in the category of heavy smokers and moderate smokers both (20.0 %), and smoking duration 10 (30.0 %).